Gambaran Rerata Kadar Kalsium Dan Fosfor Pada Pasien Yang Menjalani Hemodialisis Di Rumah Sakit Anna Medika Bekasi - Annisya, Nur; Armelia, Linda (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2018)
Background: Chronic Kidney Disease (CKD) is a pathophysiological process with a diverse etiology, resulting in slow progressive kidney function. Hemodialysis is used as a therapy to replace deteriorating renal function. PGK has high mortality and morbidity, because it can cause various complications, one of the complications of PGK is the regulation of mineral settings, especially calcium and phosphate. Methods: The type of research in this study is descriptive quantitative with cross sectional study design. The population in this study were PGK patients undergoing hemodialysis at Anna Medika Bekasi Hospital. Sample selection using simple random sampling technique with condition to fulfill inclusion criteria. Secondary data retrieval (medical record). Results: From 55 samples were 32 patients (58.2%) with hypocalcemia category, 14 patients (25.4%) with normal calcium level, 9 patients (16.4%) with hypercalcemia category, 10 patients (18.2%) with hypophosphatemia category, 4 patients (7.3% ) with normal phosphorus levels and 41 patients (74.5%) by category. Of 32 patients (58.2%) hypocalcemia and 41 (74.5%) hyperphosphatemia which decreased calcium along with a rise in phosphorus by 22 patients (40%). Conclusion: In this study it was found that patients were more likely to have hypocalcemia and hyperphosphatemia. Less than half the patients had decreased levels of calcium along with elevated levels of phosphorus.